2019
DOI: 10.1007/s00068-019-01220-3
|View full text |Cite
|
Sign up to set email alerts
|

Poor sporting abilities after tibial plateau fractures involving the posterior column: how can we do better?

Abstract: Purpose Tibial plateau fractures with the involvement of the posterior column are an important prognostic factor towards poor functional outcome. We aimed to assess the sporting abilities postoperatively with special emphasis on the type of sports and sport-specific movements, as well as time needed to resume sports, restricting factors in sports engagement, and patient satisfaction. We aimed to provide prognostic information on return to sports. Methods Demographic, clinical and radiological variables were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Less than 1 in 5 patients return to pre-injury levels of activity with reported main issues such as pain, knee joint stiffness, instability and fear for re-injury. 40 This fact illuminates the need for ongoing rehabilitation of these patients, in order to try to improve the patients’ satisfaction and level of activity.…”
Section: Discussionmentioning
confidence: 99%
“…Less than 1 in 5 patients return to pre-injury levels of activity with reported main issues such as pain, knee joint stiffness, instability and fear for re-injury. 40 This fact illuminates the need for ongoing rehabilitation of these patients, in order to try to improve the patients’ satisfaction and level of activity.…”
Section: Discussionmentioning
confidence: 99%
“…A special consideration must be taken for posterior plateau fragments which may not be adequately buttressed by medial or lateral plating. Involvement of the posterior segment has been shown to be more prevalent than previously recognized and failure to identify and manage it has been associated with misalignment and functional instability [22,32,100]. This could also be one of the reasons for failure in some fractures that still collapse secondarily after fixation [98,101].…”
Section: Open Reduction Internal Fixation (Orif)mentioning
confidence: 99%
“…Nonetheless, persistent pain, impaired range of motion (ROM), and/or instability are repeatedly described. While short-and mid-term outcomes have been associated with a low return-to-sports rate and a low patient-related outcome compared to healthy individuals (Knee Injury and Osteoarthritis Outcome Score), a good-toexcellent knee function in the long term has been reported (Rasmussen and Hospital for Special Surgery Knee Scoring System) [6][7][8][9][10]. Several studies have identified potential fracture-specific and surgery-related risk factors for impaired patient outcomes [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…While short-and mid-term outcomes have been associated with a low return-to-sports rate and a low patient-related outcome compared to healthy individuals (Knee Injury and Osteoarthritis Outcome Score), a good-toexcellent knee function in the long term has been reported (Rasmussen and Hospital for Special Surgery Knee Scoring System) [6][7][8][9][10]. Several studies have identified potential fracture-specific and surgery-related risk factors for impaired patient outcomes [6][7][8][9][10][11]. As a result, there is general consensus that anatomical reconstruction within a 2-3-mm articular step-off, a straight leg axis, and stable bony and ligamentous fixation should be considered [9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation